2011
DOI: 10.1523/jneurosci.4496-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nociceptive Transmission in Migraineurs Predicts Migraine Attacks

Abstract: Several lines of evidence suggest a major role of the trigeminovascular system in the pathogenesis of migraine. Using functional magnetic resonance imaging (fMRI), we compared brain responses during trigeminal pain processing in migraine patients with those of healthy control subjects. The main finding is that the activity of the spinal trigeminal nuclei in response to nociceptive stimulation showed a cycling behavior over the migraine interval. Although interictal (i.e., outside of attack) migraine patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
221
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(241 citation statements)
references
References 37 publications
16
221
1
2
Order By: Relevance
“…Our study found significant activation in response to trigeminal nerve somatosensory stimulation in bilateral Sp5 (oralis subnucleus). Interestingly, Stankweitz et al (20) demonstrated a positive correlation between Sp5 activity and time to next ictal event, suggesting that Sp5 response to nociceptive stimulation may be an important predictor of an upcoming migraine attack. In our study, we similarly observed a positive correlation between Sp5 activation and the interictal phase, though not specifically with time to subsequent attack (r ¼ À0.33, p ¼ 0.21).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found significant activation in response to trigeminal nerve somatosensory stimulation in bilateral Sp5 (oralis subnucleus). Interestingly, Stankweitz et al (20) demonstrated a positive correlation between Sp5 activity and time to next ictal event, suggesting that Sp5 response to nociceptive stimulation may be an important predictor of an upcoming migraine attack. In our study, we similarly observed a positive correlation between Sp5 activation and the interictal phase, though not specifically with time to subsequent attack (r ¼ À0.33, p ¼ 0.21).…”
Section: Discussionmentioning
confidence: 99%
“…52 Decreased activation of trigeminal nuclei with nociceptive stimulation. 45 Magnetic resonance angiography Dilation of extracranial middle meningeal artery and intracranial middle cerebral artery; sumatriptan-induced contraction. 35 Positron emission tomography Increased blood flow in the brainstem (midbrain and dorsal pons), cerebellum, hypothalamus, thalamus, insula, cingulate cortex, prefrontal cortex, auditory cortex, and visual association cortex (brainstem and hypothalamus activation persisting after sumatriptan injection).…”
Section: This Review Was Initiated With a Pubmed Search Of The Us Natmentioning
confidence: 99%
“…Functional MRI studies also compared brain responses during trigeminal pain processing in migraine patients with those of healthy control (HC) subjects. 45 The activity of the spinal trigeminal nuclei in response to nociceptive stimulation showed a cycling behavior over the migraine interval. Interictal patients exhibited lower activations in the spinal trigeminal nuclei compared with controls, however, preictal (shortly before attack) subjects showed activity similar to controls, indicating that the trigeminal activation level increases over the pain-free migraine interval.…”
mentioning
confidence: 99%
“…The hypothesis of a compensatory reorganization of anti-nociceptive network in migraine is supported by another BOLD-fMRI study, using repetitive trigeminal-nociceptive stimulation, which showed significant increased ACC and decreased SSC responses in MwoA patients [31]. The same authors reported a cycling behavior of the spinal trigeminal nuclei activity in response to nociceptive stimulation, demonstrating that the trigeminal activation level increases over the pain-free migraine interval [32]. More recently, Stankewitz and May [33] have investigated neuronal substrates of olfactory stimulation during migraine attack and interictal period and, at a later stage, using both trigeminonociceptive and olfactory stimuli, explored neuronal correlates of habituation in migraine subjects [34].…”
Section: Discussionmentioning
confidence: 82%